EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part II – Diagnostic Ultrasound-Guided Interventional Procedures (Short Version) - Sidhu, P. S.; Brabrand, K.; Cantisani, V.; Correas, J. M.; Cui, X. W.; D’Onofrio, M.; Essig, M.; Freeman, S.; Gilja, O. H.; Gritzmann, N.; Havre, R. F.; Ignee, A.; Jenssen, C.; Kabaalioğlu, A.; Lorentzen, T.; Mohaupt, M.; Nicolau, C.; Nolsøe, C. P.; Nürnberg, D.; Radzina, M.; Saftoiu, A.; Serra, C.; Spârchez, Z.; Sporea, I.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
This is the second part of the series on interventional ultrasound guidelines of the Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB). It deals with the diagnostic interventional procedure. General points are discussed which are pertinent to all patients, followed by organ-specific imaging that will allow the correct pathway and planning for the interventional procedure. This will allow for the appropriate imaging workup for each individual interventional procedure (Long version/ short version; the long version is published online).
Keywords: guideline; biopsy; ultrasound; aspiration; CT; MRI; needle; catheter; cancer; transplant; adrenal; liver; kidney; pancreas; lymph node; gastrointestinal tract; retroperitoneal; spleen